2022
DOI: 10.3390/ijerph19084918
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Coping Strategies among Students with Type D Personality

Abstract: Objective: Personality type D may be associated with a predisposition to develop stress under external adverse influences, for example, in the COVID-19 pandemic. Likewise, type D personality is associated with higher burnout levels; thus, it may contribute to the development of diseases symptoms. The current study was designed to examine the coping strategies in young healthy persons with personality type D. Methods: The study included 98 medical students, with 30 being males. The participants completed questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
1
7
0
2
Order By: Relevance
“…This is somewhat at odds with previous research, which found that students who were more likely to use problem-solving strategies had greater academic success [21]. Apparently, further research on this topic should use not only an expanded battery of psychophysiological tests, but also a more detailed assessment of coping strategies (for example, using the Ways of Coping Questionnaire [22,40]).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This is somewhat at odds with previous research, which found that students who were more likely to use problem-solving strategies had greater academic success [21]. Apparently, further research on this topic should use not only an expanded battery of psychophysiological tests, but also a more detailed assessment of coping strategies (for example, using the Ways of Coping Questionnaire [22,40]).…”
Section: Discussionmentioning
confidence: 79%
“…Students who experienced less stress and engaged in less cognitive avoidance and more problem solving had greater academic success; and students under more stress performed worse [21]. Our previous study demonstrated a link between type D personality and maladaptive coping strategies (escape-avoidance strategy) [22]. When performing a computer task with avatars, type D individuals had higher rates of avoidance in the avatar task than non-type D individuals [23].…”
Section: Introductionmentioning
confidence: 83%
“…In this respect, the strategies likely to have the greatest impact would be those aimed at correcting avoidance coping and at enhancing adaptive coping. It would also be advisable to reinforce family support, in order to reduce compassion fatigue and to facilitate compassion satisfaction in students during their clinical practice ( 54 , 78 ).…”
Section: Discussionmentioning
confidence: 99%
“…Таблица 5. Клинико-психологические факторы, ассоциированные с наличием субклинической или клинической депрессии, по данным бинарного логистического регрессионного анализа (метод Forward Stepwise LR) В предыдущих исследованиях при типе личности Д изучали преимущественно копинг-стратегии [6,7,11]. У здоровых лиц было отмечено, что при типе Д преобладание неадекватных стратегий преодоления стресса среди способов совладающего поведения -это стратегия «Бегство -избегание», а среди стратегий преодоления стресса -«Стратегия избегания».…”
Section: результатыunclassified
“…Поэтому основным направлением поведенческих воздействий при типе личности Д предлагается уменьшение их реакций на стрессовые воздействия. Как следствие, появились исследования по изучению когнитивной оценки и стратегий преодоления стресса как у здоровых лиц [6], так и у больных ИБС [7]. Тем не менее, исследования в данной области остаются единичными и требуют дальнейшего изучения вопроса.…”
Section: Introductionunclassified